Implementasi Sistem Informasi Nilai Akademik dan Raport Berbasis Web Menggunakan Metode Object Oriented Analysis and Design - Subarkah Abdullah; Abdurrahman Harits (Bulletin of Computer Science Research, 2026)
Managing academic grade data and creating report cards are crucial activities in educational administration, but the current process is still carried out conventionally using spreadsheet applications. This method of working causes various problems such as long processing time, high risk of calculation errors, and difficulties in storing and tracking historical data. This study aims to design, build, and implement a web-based information system that is able to automate grade processing and report card creation to be faster, more accurate, and more integrated. The method applied in developing this system is Object Oriented Analysis and Design (OOAD) with modeling using the Unified Modeling Language (UML), and implementation using the PHP programming language and MySQL database. The main contribution of this research lies in the development of a web-based academic information system specifically designed to meet the characteristics of vocational high school administration, by applying the Object-Oriented Analysis and Design (OOAD) approach and structured UML modeling. The resulting system not only automates grade processing and report card printing, but also provides a modular, integrated, and easily developed software architecture to support the ongoing digitalization of educational administration.